Place-attachment as a conservation effort in the children's story series "Bait al-Ahdhar": Lawrence Buell’s ecocritical perspective - Habibullah, Moh. Rifqi; Munjiah, Ma'rifatul (LITERA, 2025)
Children’s understanding of the relationship between humans and the environment is a significant factor in fostering ecological awareness, which forms the foundation for future environmental coservation efforts. This research aims to describe and identify place-attachment as an effort for environmental conservation in the Bait al-Ahdhar children’s story series based on Lawrence Buell’s ecocriticial perspective. The type of research used in this study is descriptive qualitative with the ecocriticism approach. The primary data source is the Bait al-Ahdhar children’s story series by Hadil Ghanim and Walid Tahir, with additional data drawn from books, journals, and relevant scientific articles. The data collection technique involves a thorough reading and note-taking process. The data analysis technique employs the Miles, Huberman and Saldaña model, which consists of data condensation, data display, and conclusion/verification. The results of this research indicate the presence of four dimensions of place-attachment as a conservation effort in the children’s story series Bait al-Ahdhar: (1) Concentric Areas, as evidenced by a child’s greater concern for the cleanliness of their bedroom compared to their house and the surrounding streets, (2) Local Archipelagos, as evidenced by a child’s concern for the school environment based on a sense that school is like a second home, (3) The Historicity of Places, as evidenced by a child’s concern for the worsening environmental changes in the city, and (4) Temporal Accumulation, as evidenced by a child’s concern for the school environment based on learning and playing experiences in previous class. These findings suggest that place-attachment may serve as a solution for children in environmental conservation.